Evaluation of medication-related osteonecrosis of the jaw using the Japanese Adverse Drug Event Report database - Inada A; Hosohata K; Oyama S; Niinomi I; Mori Y; Yamaguchi Y; Uchida M; Iwanaga K (Dove Medical Press, 2018)
Ayaka Inada, Keiko Hosohata, Saki Oyama, Iku Niinomi, Yasuhiro Mori, Yuki Yamaguchi, Mayako Uchida, Kazunori Iwanaga Education and Research Center for Clinical Pharmacy, Osaka University of Pharmaceutical Sciences, Takatsuki, Osaka 569-1094, Japan Background: Bisphosphonates (BPs) and denosumab are widely used to treat osteoporosis and complications associated with bone metastases. However, medication-related osteonecrosis of the jaw (MRONJ) is a serious problem. Objective: The objective of this study was to evaluate the frequency, outcome, and characteristics of patients with drug-induced MRONJ. Methods: Retrospective pharmacovigilance disproportionality analysis was conducted using the Japanese Adverse Drug Event Report (JADER) database from the Pharmaceuticals and Medical Devices Agency. Adverse event reports submitted to JADER between 2004 and 2017 were analyzed, and the reporting odds ratio (ROR) was calculated. Results: Among the BPs that cause MRONJ, zoledronate was the most common; therefore, we compared the characteristics of cases of MRONJ induced by zoledronate with those induced by denosumab. Among the 3,875 (68.1% women) cases of MRONJ, zoledronate-related MRONJ accounted for 1,283 (56.0% women) and denosumab-related MRONJ accounted for 322 (55.3% women). MRONJ was more frequent after 70 years of age regardless of the use of either zoledronate or denosumab; onset occurred after 1 year from the denosumab treatment, but it is unknown when onset occurred after zoledronate treatment. The outcomes for MRONJ were poor, with 406 reports on zoledronate (31.6%) and 152 reports on denosumab (47.2%) demonstrating nonrecovery. Zoledronate (ROR: 319.3, 95% CI: 296.0–344.4) had the highest ROR among BP agents. Denosumab had a high ROR (ROR: 155.2, 95% CI: 136.5–176.3). Zoledronate and denosumab were used in similar patient backgrounds, and their use resulted in a similar frequency of MRONJ. Conclusion: The findings of this comprehensive evaluation of MRONJ using the JADER database will be helpful for prescribing medications to elderly patients. Keywords: medication-related osteonecrosis of the jaw, pharmacovigilance, spontaneous reporting system, reporting odds ratio, Japanese Adverse Drug Event Report database